2009
DOI: 10.1016/j.ijid.2008.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside reverse transcriptase inhibitor resistance mutations in subtype F1 strains isolated from heavily treated adolescents in Romania

Abstract: Although the overall resistance mutations were not different from those described for subtype B, the subtype F1 HIV-1 NRTI mutation patterns displayed same specificities with possible therapeutic consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Unrelated to the Brazilian epidemic, sub-subtype F1 was initially introduced and spread among adult heterosexuals in Romania. In this Eastern-European country, it subsequently reached a very high prevalence rate of more than 70% due to several major outbreaks among children in orphanages and people using intravenous drugs (Dumitrescu et al, 1994; Bandea et al, 1995; Apetrei et al, 1998; Op De Coul et al, 2000; Guimarães et al, 2009; Paraschiv et al, 2009; Mehta et al, 2011; Mbisa et al, 2012; Niculescu et al, 2014). Both Brazil and Romania were at the origin of the F1 epidemic in Italy, where Brazilian strains contributed to many more introduction events characterized with a more extensive spread (Lai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unrelated to the Brazilian epidemic, sub-subtype F1 was initially introduced and spread among adult heterosexuals in Romania. In this Eastern-European country, it subsequently reached a very high prevalence rate of more than 70% due to several major outbreaks among children in orphanages and people using intravenous drugs (Dumitrescu et al, 1994; Bandea et al, 1995; Apetrei et al, 1998; Op De Coul et al, 2000; Guimarães et al, 2009; Paraschiv et al, 2009; Mehta et al, 2011; Mbisa et al, 2012; Niculescu et al, 2014). Both Brazil and Romania were at the origin of the F1 epidemic in Italy, where Brazilian strains contributed to many more introduction events characterized with a more extensive spread (Lai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These ARL perform approximately 90% of the HIV-1 drug resistance testing in Belgium. HIV-1 sub-subtype F1 pol sequences were requested from partners in other European and African countries where circulation of F1 infections has been reported (Palma et al, 2007; Paraschiv et al, 2009; Frentz et al, 2010; Lai et al, 2012; Ivanov et al, 2013; Sayan et al, 2013; Alexiev et al, 2015). Furthermore, all available HIV-1 sub-subtype F1 pol sequences were extracted from the Los Alamos HIV Sequence Database (LANL) 1 (Triques et al, 1999; Montano et al, 2005; Aulicino et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…These hydrogel polymers can have reactive groups on the surface which enable the nanoparticles to be converted to stimuli-responsive particles and they can also be made targetable by attaching receptor-specific ligands. The preparation of nanoparticles from chitosan, a hydrogel polymer, for drug delivery can have several advantages over the use of chitosan microspheres and microcapsules [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates showed that 962 779 people including 104 937 children were in need of ART in Zimbabwe in 2013 (based on CD4 counts ≤ 350 cells/ml), and projections showed that the number of people in need of ART will increase to 1.3 million and 1.4 million in 2014 and 2015, respectively [5]. With the rapid scale up of ART over the years, the emergence of antiretroviral (ARV) drug resistance mutations in Zimbabwe has been inevitable as in any other settings [7, 8]. Treatment failure may result from acquired drug resistant mutations due to ARV drug pressure and such variants of the virus can also be transmitted to newly infected individuals who are not yet on ART as transmitted drug resistance [9, 10].…”
Section: Introductionmentioning
confidence: 99%